Directors' remuneration: the need for a geo-political perspective - Kakabadse, Nada K.; Kakabadse, Andrew P.; Kouzmin, Alexander (Emerald Group Publishing Limited, 2004)
There are many ways to construct an incentive program. However, most compensation plans tend to be focused on profitability and profitability-related accomplishments with little or no incentive for corporate social responsibility. Director's compensation continues to climb with the United States leading and Britain following modestly behind. The question as to where fair pay ends and over-compensation begins – and what that means for the community – is rarely raised. In order to understand the impact of fair and over-compensated director's pay on other stakeholders, a geo-political perspective is proposed that builds on knowledge of existing theories of the firm.
Keywords: Chief executives; Incentive schemes; Remuneration